PENGARUH LATIHAN RUNNING ABC TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS VIII SMPIT BINA ILMI PALEMBANG - Niku Saputra; Suparman Suparman; Rais Firlando ($$8@@&&$%K, 2022)
The purpose of this study is to determine the effect of Running ABC training on the results of long jump squatting style of grade VIII students of SMPIT Bina Ilmi Palembang athletics according to the schedule and training method that has been given. This type of research is true experimentation with the design of this study pre-test and post-test control. With a population of all male students of SMPIT Bina Ilmi Palembang amounting to 60 people or 100% of the population, which is divided into two groups using simple random sampling. All samples were pre-tested and then the results were ranked from farthest to closest. After being treated for 5 weeks that there was an Effect of ABC Running Training on the Results of Long Jump Squatting Style of Class VIII Students of SMPIT Bina Ilmi Palembang.